2008
DOI: 10.1111/j.1365-2966.2007.12743.x
|View full text |Cite
|
Sign up to set email alerts
|

AMI limits on 15-GHz excess emission in northern H ii regions

Abstract: We present observations between 14.2 and 17.9 GHz of 16 Galactic H ii regions made with the Arcminute Microkelvin Imager. In conjunction with data from the literature at lower radio frequencies we investigate the possibility of a spinning dust component in the spectra of these objects. We conclude that there is no significant evidence for spinning dust towards these sources and measure an average spectral index of α= 0.15 ± 0.07 (where S∝ν−α) between 1.4 and 17.9 GHz for the sample.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…The majority of AME sources are diffuse, including the Perseus and ρ Ophiuchi clouds; Tibbs et al (2010) found that in the Perseus molecular cloud at least 90% of the AME comes from diffuse extended emission. Surveys at higher resolution do not appear to detect strong AME; Scaife et al (2008) found little or no detectable AME from a sample of relatively compact ( 1 ) H ii regions.…”
Section: Statistical Study Of Ame Regionsmentioning
confidence: 88%
See 2 more Smart Citations
“…The majority of AME sources are diffuse, including the Perseus and ρ Ophiuchi clouds; Tibbs et al (2010) found that in the Perseus molecular cloud at least 90% of the AME comes from diffuse extended emission. Surveys at higher resolution do not appear to detect strong AME; Scaife et al (2008) found little or no detectable AME from a sample of relatively compact ( 1 ) H ii regions.…”
Section: Statistical Study Of Ame Regionsmentioning
confidence: 88%
“…Although this is a considerable fraction, it is less than what has been observed in the diffuse Galactic foreground at high latitudes, where the dust-correlated AME is the dominant component and accounts for approximately 75% of the total 30 GHz emission (Davies et al 2006;Ghosh et al 2012). On the other hand, other measurements (Dickinson et al 2007;Scaife et al 2008) have found much less or no AME as a fraction of the total flux density. Sources with a smaller AME fraction ( 20%) may be prevalent, but are much more difficult to detect since the other non-AME components must be accurately removed first.…”
Section: Ame Fraction and Ire -H II Or Molecular Dust Clouds?mentioning
confidence: 90%
See 1 more Smart Citation
“…Even though AME has been detected on arcmin scales (Scaife et al 2009;Tibbs et al 2013), the emission appears to be correlated with the strength of the radiation field rather than the column of small grains/PAHs along some sight-lines (Tibbs et al 2011(Tibbs et al , 2012. Also, in some objects (such as compact HII regions), the data have failed to detect AME at all (Scaife et al 2008). The AME could also be due to another mechanism, such as thermal fluctuations in magnetic grains (a.k.a.…”
Section: Introductionmentioning
confidence: 92%
“…Anomalous emission was first proposed by Draine & Lazarian (1998) to come from rapidly rotating PAHs (Rouan et al 1992), the spinning dust grains. Since, it has been observed in various interstellar environments: dark clouds (Watson et al 2005;Casassus et al 2006;Scaife et al 2009;Dickinson et al 2010); H ii regions Scaife et al 2008); planetary nebulae (Casassus et al 2007) and diffuse ISM (Miville-Deschênes et al 2008). Several processes can excite or damp the grains' rotation: pho- Fig.…”
Section: Anomalous Microwave Emissionmentioning
confidence: 99%